Semisynthesis of a mellein-type 3,4-dihydroisocoumarin from cashew nut shell liquid (CNSL) - Mgina, Clarence A.; Kadir, Fatma (Tanzania Journal of Science, 2018)
Mellein-type 3,4-dihydroisocoumarin 39 (i.e., 8-methoxy-3-tridecyl-3,4-dihydroisocoumarin or 8-methoxy-3-tridecylisochroman-1-one), and its precursors, namely, methyl 2-methoxy-6-pentadecylbenzoate (37), methyl 2-methoxy-6-pentadecanoylbenzoate (38) and (E)-methyl 2-methoxy-6-(pentadec-1-enyl)benzoate (19) were synthesized from anacardic acid (12) as a starting material obtained from Cashew Nut Shell Liquid (CNSL) in an overall yield of 78%. The transformation of 12 to 39 involved protection of the reactive phenolic and carboxylic acid groups of compound 12 through methylation followed by hydrogenation so as to saturate the mono-, di- and tri-unsaturated C15 chains of anacardic acid (12). Subsequent benzylic oxidation and reduction of the keto functional group with concomitant dehydration of the alcohol led to the formation of 19,which after deprotection of the carboxyl group followed by lactonization, gave the mellein-type 3,4-dihydroisocoumarin 39.